Emotional Intelligence and Mindfulness: Relation and Enhancement in the Classroom With Adolescents - Rodríguez-Ledo, César; Orejudo, Santos; Cardoso, Maria Jesús; Balaguer, Álvaro; Zarza-Alzugaray, Javier (Frontiers in Psychology, 2018)
Emotional Intelligence (EI) and mindfulness are two constructs that have been studied separately and so the relation be-tween them remains still unclear. Besides, research in the area has not tried to further deepen about how the enhancement of EI and mindfulness together can reach better improvements in this ability to attend mindfully. In other to fill this gap of knowledge, the goal of this research was to study the relationship between EI and mindfulness competence in the sample as well as to assess the impact of the implementation of the EI and mindfulness competences developmental Program (SEA) on the mindfulness competence of the participants. Regarding methodology, the sample consisted on 156 adolescents, aged 11 to 14 years old, who were students in a Spanish public High School. 108 participants were randomly assigned to the experimental condition and the other 48 were assigned two to the control condition. The instruments used to evaluate EI were the CDE-SEC, EQi-Youth Version and general empathy scale. The mindfulness in school scope scale was used to assess mindfulness competences. Social adaptation was evaluated by using the social abilities and adjustment questionnaire BAS3. All the instruments where answered by the participants and are adapted to a young sample of such age specifications. In relation to the results, it was detected that EI and mindfulness were related in a large number of the variables measured by the instruments. In particular, it was proven that showing a good mindfulness competence was related to owning a good general level of trait emotional intelligence. It was also related to many of the social and emotional variables assessed. Besides, the data indicated the significant relation between mindfulness competence and having better general empathy skills or being better socially adjusted to the school context. Moreover, the data found a significant effect in the interior and kinesthetic mindfulness competence of the participants after the implementation of the SEA Program. These findings corroborate the relationship between EI and mindfulness as well as the possibility of enhancing mindfulness through the application of a direct intervention Program within the classroom.